(3GSJbUGA GdfXQ aj GdbVGA hGdbOQs - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg GdYdje GdZaGQ(B... (3hHYO aEfg deG cGf GdSdWGf (B... (3TGgfTGg GdeYXe(B... (3GdCOdI GdOGdI Ydi Cf ddYHO GNJjGQ aj CaYGdg(B... (3SGQYJ aj EfTGA gPg GdQSGdIs
(3BNQgG (B:s
(3EPG de jcf GdYHO HGNJjGQg aEf GdSdWGf ZPG CeQ hRjQg Cf jaYd aYdG jchf GdhRjQ ajg eNJGQ dG eLHhQG(B... (3hdjcf gPG BNQ eG fhQOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3GdCYdGe(B: (3L(B2(3, (B227s
(3gOjI GdYGQajf(B: (3L(B1(3, U(B284s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds